A Simple System for Automatic Exam Scoring Using Optical Markup Reader - Gjorgjevikj, Dejan; Grcevski, Nikola; Mihajlov, Dragan (My University, 2000)
Probably the most efficient way to test somebody's knowledge, about some specific area or to retrieve somebody's opinion is to make a test specially created for that purpose. The test processing is very resourceful and time-consuming operation, what is making automatic test processing procedures present for a long time. The test forms used for today's common test processing machines are generally expensive, have special form and are usually printed in color. These problems lead us to create a simple, efficient and inexpensive program for automatic test processing and exam scoring.
Keywords: optical markup reading, exams, test, scoring